2016
DOI: 10.1002/hbm.23458
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of human right hippocampal/parahippocampal theta rhythm in environmental encoding during virtual spatial navigation

Abstract: Low frequency theta band oscillations (4-8 Hz) are thought to provide a timing mechanism for hippocampal place cell firing and to mediate the formation of spatial memory. In rodents, hippocampal theta has been shown to play an important role in encoding a new environment during spatial navigation, but a similar functional role of hippocampal theta in humans has not been firmly established. To investigate this question, we recorded healthy participants' brain responses with a 160-channel whole-head MEG system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 94 publications
(143 reference statements)
5
44
1
Order By: Relevance
“…One might reasonably ask if the dorsal-ventral differences in the rodent hippocampus can be expected to apply to humans; in humans the ventral region (adjacent to the amygdala) has undergone relatively greater expansion compared to the dorsal portions of the hippocampus [for a review, see Box 1 in Strange et al (2014)]. Functional imaging and lesion data has suggested the posterior hippocampus in humans shows preferential activity during spatial navigation in the nondominant hemisphere (Abrahams et al, 1997;Pu et al, 2017), although this has not reliably been demonstrated for verbal memory tasks in the dominant hemisphere or with intracranial EEG, in which aggregated hippocampal electrodes have been shown to exhibit theta power decreases and gamma band power increases during memory encoding (Sederberg et al, 2007). However, to our knowledge, there has not been a systematic attempt to differentiate anterior and posterior hippocampal electrodes and directly compare oscillatory effects.…”
Section: Results In Rodents Include the Observation That Place Cells mentioning
confidence: 99%
See 2 more Smart Citations
“…One might reasonably ask if the dorsal-ventral differences in the rodent hippocampus can be expected to apply to humans; in humans the ventral region (adjacent to the amygdala) has undergone relatively greater expansion compared to the dorsal portions of the hippocampus [for a review, see Box 1 in Strange et al (2014)]. Functional imaging and lesion data has suggested the posterior hippocampus in humans shows preferential activity during spatial navigation in the nondominant hemisphere (Abrahams et al, 1997;Pu et al, 2017), although this has not reliably been demonstrated for verbal memory tasks in the dominant hemisphere or with intracranial EEG, in which aggregated hippocampal electrodes have been shown to exhibit theta power decreases and gamma band power increases during memory encoding (Sederberg et al, 2007). However, to our knowledge, there has not been a systematic attempt to differentiate anterior and posterior hippocampal electrodes and directly compare oscillatory effects.…”
Section: Results In Rodents Include the Observation That Place Cells mentioning
confidence: 99%
“…There is an extensive literature describing the memory deficits associated with seizure onset or lesions in either dominant or nondominant hemisphere (Bonelli et al, ; Abrahams et al, ; Pu et al, ). Commensurate with these clinical observations, right lateralized hippocampal oscillations have been observed in humans in spatial memory tasks (Cornwell, Johnson, Holroyd, Carver, & Grillon, ; Ekstrom et al, ; Jacobs et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetoencephalography (MEG) has excellent temporal specificity, and previous MEG studies using healthy participants have found early amygdala activation in response to emotional faces (Garrido et al, 2012; Garvert et al, 2014; Luo et al, 2007, 2010), consistent with face processing studies that used intracranial recordings (Hesse et al, 2016; Mendez-Bertolo et al, 2016; Pourtois et al, 2010; Sato et al, 2011). Substantial evidence supports the capability of MEG to detect neural activity in deep brain structures (Badura-Brack et al, 2017; Cornwell et al, 2012a, 2012b, 2014; Dalal et al, 2008; McDermott et al, 2016; Proskovec et al, 2016; Pu et al, 2017; Salvadore et al, 2009, 2010; Wilson et al, 2009, 2010, 2011, 2017). One such MEG study used a seed-based functional connectivity approach found that veterans with PTSD had increased functional connectivity relative to veterans without PTSD between the amygdala and ventromedial prefrontal cortex when viewing threatening faces (Dunkley et al, 2016); however, this study did not examine the time course or amplitude or amygdala responses, and thus such data remains unavailable in patients with PTSD.…”
Section: Introductionmentioning
confidence: 89%
“…The environment of each condition in the 6 two training sets was the same, thus the environment in the first training set was 7 defined as new environment and that in the second one as familiar environment. 8 Therefore, the difference between the two training sets allowed us to measure 9 learning of the environment (Pu et al, 2017), and the difference between hidden 10 platform condition and random swimming condition provided an index of 11 goal-directed spatial navigation (Cornwell et al, 2008). To avoid the possibility that 12 environment learning was confounded with learning a specific location, the location 13 of the hidden platform was changed and counterbalanced between the training sets.…”
mentioning
confidence: 99%